2020
DOI: 10.1021/acs.jpca.0c07361
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reactions in the HBr+ (DBr+) + HBr System: A State-Selective Investigation of the Role of Rotation

Abstract: Self-reactions observed in the HBr + (DBr + ) + HBr system have been investigated using a guided ion-beam experiment under single-collision conditions. The reaction channels observed are proton transfer/hydrogen abstraction (PT/HA) in the case of HBr + and deuteron transfer/hydrogen abstraction (DT/HA) and charge transfer (CT) in the case of DBr + . HBr + /DBr + ions have been formed with rotational energies selected using the resonance-enhanced multiphoton ionization (REMPI) formation process. Cross sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The potential energy profile of the bimolecular collision HBr + + HCl is compared with reactions of similar sort, namely, the (self) HCl + + HCl and HBr + + HBr reactions. As stated in section , these two reactions have been studied with guided beam experiments and AIMD simulations, and they are reported to respond differently to rotational excitations. , The most obvious differences between the two self-reactions and the HBr + + HCl collisions are the simplification of the potential energy profiles. For example, the p2 and p3 in the self-reactions would become one single product, H 2 Cl + (H 2 Br + ) + Cl (Br).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The potential energy profile of the bimolecular collision HBr + + HCl is compared with reactions of similar sort, namely, the (self) HCl + + HCl and HBr + + HBr reactions. As stated in section , these two reactions have been studied with guided beam experiments and AIMD simulations, and they are reported to respond differently to rotational excitations. , The most obvious differences between the two self-reactions and the HBr + + HCl collisions are the simplification of the potential energy profiles. For example, the p2 and p3 in the self-reactions would become one single product, H 2 Cl + (H 2 Br + ) + Cl (Br).…”
Section: Resultsmentioning
confidence: 99%
“…11−14 For example, the collision of HBr + + HBr could form Br + H 2 Br + through proton transfer (PT) and hydrogen abstraction (HA) or HBr + HBr + through charge transfer (CT) and hydrogen exchange (HE). 14 It has been reported that as the rotational energy increases, the combined PT/HA reactivity monotonically decreases, while the combined CT/HE reactivity increases. 14 However, the impact of the rotational energy is quite different in a similar reaction, HCl + + HCl, whose PT/ HA reactivity demonstrates a local minimum.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations